Charting the psychological literacy landscape: Systematic review highlighting psychology education - Cranney, Jacquelyn; Morris, Sue; Norris, Kimberley; Connolly, Caitlin E. (Frontiers in Education, 2022)
The aim of this systematic review is to provide, for the first time, a broad overview of the scope and nature of the current English language concept of ‘psychological literacy' (PL) as evidenced in the literature, primarily since 2010. Covidence systematic review methodology yielded 112 papers that were scored on 23 specific criteria/questions relevant to addressing predetermined research questions. PL has been conceptualized as both a general capability (e.g., ethical application of psychological knowledge) and a group of capabilities (discipline-specific knowledge and research methods, and more generic capabilities such as communication). Variability in the constellation of group capabilities has led to challenges in operationalization and thus measurement, signaling the need for international consensus and improved measurement. We propose a model for how PL is related to psychologically literate citizenship and global citizenship. Key papers explore PL as an integrative concept in psychology. All papers were relevant to psychology education, with most prevalent being undergraduate level, and least prevalent being graduate level. There were numerous papers providing practical PL teaching and assessment strategies. PL as a pedagogical approach has been a necessary and richly diverse focus. Finally, a revisioning of PL within the context of psychology education, as well as recommendations for further research and development, are suggested.